Comparative accuracy of pleural fluid unstimulated interferon-gamma and adenosine deaminase for diagnosing pleural tuberculosis: A systematic review and meta-analysis. - Ashutosh Nath Aggarwal (Public Library of Science (PLoS), 2021)
Objective We compared diagnostic accuracy of pleural fluid adenosine deaminase (ADA) and interferon-gamma (IFN-γ) in diagnosing tuberculous pleural effusion (TPE) through systematic review and comparative meta-analysis. Methods We queried PubMed and Embase databases to identify studies providing paired data for sensitivity and specificity of both pleural fluid ADA and IFN-γ for diagnosing TPE. We used hierarchical summary receiver operating characteristic (HSROC) plots and HSROC meta-regression to model individual and comparative diagnostic performance of the two tests. Results We retrieved 376 citations and included 45 datasets from 44 publications (4974 patients) in our review. Summary estimates for sensitivity and specificity for ADA were 0.88 (95% CI 0.85-0.91) and 0.91 (95% CI 0.89-0.92), while for IFN-γ they were 0.91 (95% CI 0.89-0.94) and 0.96 (95% CI 0.94-0.97), respectively. HSROC plots showed consistently greater diagnostic accuracy for IFN-γ over ADA across the entire range of observations. HSROC meta-regression using test-type as covariate yielded a relative diagnostic odds ratio of 2.22 (95% CI 1.68-2.94) in favour of IFN-γ, along with better summary sensitivity and specificity figures. No prespecified subgroup variable significantly influenced the summary diagnostic accuracy estimates. Conclusion Pleural fluid IFN-γ estimation has better diagnostic accuracy than ADA estimation for diagnosis of TPE.